Influence of philosophy in the use of nursing technology: integration review (Research, Society and Development, 2020)
To analyze the influence of philosophy on the use of technology in nursing. This is an integrative review, whose fundamental question was "How does philosophy influence the use of technology in nursing?". Data collection took place in July 2017 in the databases: Latin American and Caribbean Literature in Health Sciences, Electronic Scientific Library Online, Cumulative Literature Index in Nursing and Allied Health and International System of Analysis and Recovery of Medical Literature Online via PubMed. A research was carried out through the descriptors: Philosophy in nursing, Technology and Nursing team and after inclusion and exclusion, including part of the results 12 articles. A scientific research in nursing to use technologies to perform care, both for medium-sized equipment, computer programs, as well as technologies such as alternative therapies, health education, among others. Scientific production shows different forms of use as technologies in nursing and its importance in the practice of quality care and assistance to patients.